LOCAL NEEDS AND GLOBAL CHALLENGES: HOW NEXT GENERATION ITALIA ADDRESSES THE TERRITORIAL DISPARITIES. A RESILIENT REINTERPRETATION OF THE REGGIO CALABRIA METROPOLITAN STRATEGY - Bevilacqua, Carmelina; Romeo, Ilaria (BDC. Bollettino Del Centro Calza Bini, 2021)
This paper aims at providing a conceptual framework to display how the Italian plan for recovery, under the next-generation goals, can “absorb” the disparities inside each regional context and how the local systems can differentiate the response to global challenges. The transition towards a more sustainable and innovative Europe is the main objective of the European Union and its policies. Considering the two pressing crises to tackle, namely, climate change and the COVID-19 pandemic, transformative development is gaining increasing momentum. Nowadays, processes of adaptation and transition are increasingly driving urban and territorial transformations. A reinterpretation of the Reggio Calabria Metropolitan Strategy is proposed to sharpen spatial targeting towards resilience and transition in a particular “fragile” context. Keywords: recovery and resilience, urban transition, transformative policy